2018
DOI: 10.1292/jvms.17-0661
|View full text |Cite
|
Sign up to set email alerts
|

Restraint stress in lactating mice alters the levels of sulfur-containing amino acids in milk

Abstract: It is well known that maternal stress during the gestation and lactation periods induces abnormal behavior in the offspring and causes a lowering of the offspring’s body weight. Various causes of maternal stress during the lactation period, relating to, for example, maternal nutritional status and reduced maternal care, have been considered. However, little is known about the effects on milk of maternal stress during the lactation period. The current study aimed to determine whether free amino acids, with spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…A total of 151 pups (control: 76, male: 38; female: 38; antibiotics: 75, male: 38; female: 37) were delivered on the same due day and were weaned at postnatal day 21 (P21). At P2, the gender of neonatal animals was confirmed according to the copulatory plugs (Nishigawa et al., 2018). Pups were standardized ( n = 8 [6 male + 2 female] neonatal mice/dam) to receive the equivalent amount of feeding and maternal care.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 151 pups (control: 76, male: 38; female: 38; antibiotics: 75, male: 38; female: 37) were delivered on the same due day and were weaned at postnatal day 21 (P21). At P2, the gender of neonatal animals was confirmed according to the copulatory plugs (Nishigawa et al., 2018). Pups were standardized ( n = 8 [6 male + 2 female] neonatal mice/dam) to receive the equivalent amount of feeding and maternal care.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, restraint stress in lactating mice caused an increase in the concentration of taurine and cystathionine in milk. However, restraint stress did not alter their concentration in the maternal plasma, liver, and mammary glands [ 73 ]. The ratio of taurine concentration in breast milk to its concentration in maternal plasma was significantly increased in the restraint stress group, suggesting that maternal stress promoted taurine transportation from maternal blood into milk [ 73 ].…”
Section: Transport Of Taurine From Mothers To Offspringmentioning
confidence: 99%
“…However, restraint stress did not alter their concentration in the maternal plasma, liver, and mammary glands [ 73 ]. The ratio of taurine concentration in breast milk to its concentration in maternal plasma was significantly increased in the restraint stress group, suggesting that maternal stress promoted taurine transportation from maternal blood into milk [ 73 ]. Although the detailed molecular mechanisms underlying this phenomenon remain to be elucidated, the enhanced transport of taurine into milk under maternal stress conditions may be associated with the upregulation of the activity of TauT by the stress hormone, cortisol, at the cellular level as described above [ 36 ].…”
Section: Transport Of Taurine From Mothers To Offspringmentioning
confidence: 99%
“…Concentrations of most individual free amino acids steadily decreased with the progression of lactation [31]. In addition, restraint stress in lactating mice caused changes in the free amino acid metabolism and in the transportation of sulfur-containing amino acids and resulted in higher taurine (Tau) concentration in milk [25]. Considering all these results, it was suggested that free amino acid concentrations in milk can be modified by several factors.…”
mentioning
confidence: 99%
“…In addition, the relationships between free amino acid concentrations in plasma and depression or injection of antidepressants were investigated using male WIS and WKY rats [18]. However, free amino acid concentration in the milk could not be predicted by the free amino acid concentration in plasma, since the pattern of free amino acids was mostly different between milk and plasma [17, 25]. This fact suggested that free amino acids in plasma are used for milk protein synthesis and/or are metabolized differently for each free amino acid.…”
mentioning
confidence: 99%